The Potential and Reality for the Inclusion of Service Users in Social Work - Granosik, Mariusz; Gulczyńska, Anita; Kostrzyńska, Małgorzata; Littlechild, Brian (Participatory Social Work: Research, Practice, Education, 2019)
This chapter sets out to examine the potential and the reality for the inclusion of service users in social work services, social work education, and social work research. It includes special reference to such work with the most vulnerable service users, for example certain people with mental health problems. The chapter will critically examine the theoretical framework, potential of, and reality for, the inclusion of service users in social work services, social work education, and social work research. The discussion will critically analyse the rationale, challenges and opportunities of involving service users and carers in such areas using ideas around the ethics of social work as set out in the International Federation of Social Worker’s (IFSW)/International Association of Schools of Social Work’s (IASSW) Ethical Codes (2012) and their Definition of Social Work (2014) and further analyzed against S. Arnstein’s “ladder of participation”. In examining how we can work towards the greatest level of participation in co-production, the chapter will use examples from projects carried out by the author.